A public good version of the collective household model: an empirical approach with an application to British household data - Chris van Klaveren; Bernard van Praag; Henriëtte Maassen van den Brink (Institute for the Study of Labor (IZA), 2008)
In this paper we consider an empirical collective household model of time allocation for two-earner households. The novelty of this paper is that we estimate a version of the collective household model, where the internally produced goods and the externally purchased goods are assumed to be public. The empirical results suggest that: (1) Preferences of men and women differ; (2) Although there are significant individual variations, on average the utility functions of men and women are equally weighted in the household utility function; (3) Differences in the ratio of the partners' hourly wages are explanatory for how individual utilities are weighted in the household utility function. (4) The female's preference for household production is influenced by family size, but this does not hold for the male; (5) Both the male and the female have a backward-bending labor supply curve; (6) Labor-supply curves are forward-bending with respect to the partner's wage rate; (7) Our model rejects the unitary Slutsky symmetry condition.
Keywords: D12; 330; Collective household models; household behavior; labor supply; intra-household; time allocation; Haushaltsökonomik; Öffentliches Gut; Arbeitsangebot; Zeitallokation; Privater Haushalt; Schätzung; Großbritannien